" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
3x-12-4x+10= -4
3x-4x=-4+12-10
-1x=-2 \ :(-1)
x=2
b) 4x+5-(3x+6)=2(2+x)-4
4x-15x+30=4+x-4
4x-15x-x=4-4+15-30
-12x=-15 \:-12
x=......
d) x(7+2x)=2(x-1)+1
7x+2x=2x-2+1
7x+2x-2x=-2+1
7x=-1 /: 7
x=....
3x - 12 - 4x + 10 = -4
3x - 4x = -4 + 12 - 10
-x = -2 /*(-1)
x = 2
b) 4x + 5 - (3x+6) = 2(2+x) - 4
4x + 5 - 3x - 6 = 4 + 2x - 4
4x - 3x - 2x = 4 - 4 - 5 + 6
-3x = 1 /:(-3)
x = - 1/3
c) 4 - 5(3 - x) < -x - (3-2x)
4 - 15 + 5x < -x - 3 + 2x
5x + x - 2x < -3 - 4 + 15
4x < 8 /:4
x = 2
d) x - (7+2x) = 2(x-1) + 1
x - 7 - 2x = 2x - 2 + 1
x - 2x - 2x = - 2 + 1 + 7
-3x = 6 /:(-3)
x = -2
e) x - 4/2 + 6 -x/3 = 2x - 5/6
x - 2 + 6 - x/3 = 2x - 5/6
x - x/3 - 2x = -5/6 + 2 - 6
-x - x/3 = -5/6 + 1 6/6 - 6
-x - x/3 = 1 1/6 - 6
-x - x/3 = 1 1/6 - 5 6/6
-x - x/3 = -4 5/6 /*3
-3x - x = -29/2
-4x = -29/2 /:(-4)
x = -29/2 * (-1/4)
x = 29/8 = 3 5/8
f) 5 - x + 5/3 < 2 - x
-x + x < 2 - 5 - 5/3
0 < - 4 2/3
g) 2x - 3x - 7/4 = x + 1
2x - 3x - x = 1 + 7/4
-2x = 2 3/4 /:(-2)
x = 11/4 * (-1/2)
x = - 11/8 = -1 3/8